2023
DOI: 10.1177/1179173x231179676
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to E-Cigarette Advertising and Its Association With E-Cigarette Use Among Youth and Adolescents in Two Largest Cities in Vietnam 2020

Abstract: BACKGROUND E-cigarette products have become more popular due to the marketing campaigns on various sources but caused adverse health impacts to users, especially adolescents and youths. This paper aims to describe the situation of exposure to e-cigarette advertisements of youth and adolescents living in two cities of Hanoi and Ho Chi Minh in 2020 and identify the associated factors of e-cigarette marketing with e-cigarettes use in these groups. METHODOLOGY This was a cross-sectional study. The study participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…49 Websites and social media have been used to promote and directly sell NVPs and nicotine e-liquids to young people in ASEAN LMICs, particularly in Indonesia, 50 51 where these online platforms advertise vape stores where youth can try and buy these products. 43 Evidence has also demonstrated that exposure to these marketing tactics influences young people's knowledge of NVPs in Indonesia, 48 Thailand 52 and Cambodia 53 and has been associated with NVP use among young people in Indonesia 54 and Vietnam, 55 but not among Thai university students. 56 Similar to other jurisdictions, 57 ASEAN countries have adopted various regulatory stances in response to the rise of NVPs, with policies ranging from prohibitionist to partial restrictions.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…49 Websites and social media have been used to promote and directly sell NVPs and nicotine e-liquids to young people in ASEAN LMICs, particularly in Indonesia, 50 51 where these online platforms advertise vape stores where youth can try and buy these products. 43 Evidence has also demonstrated that exposure to these marketing tactics influences young people's knowledge of NVPs in Indonesia, 48 Thailand 52 and Cambodia 53 and has been associated with NVP use among young people in Indonesia 54 and Vietnam, 55 but not among Thai university students. 56 Similar to other jurisdictions, 57 ASEAN countries have adopted various regulatory stances in response to the rise of NVPs, with policies ranging from prohibitionist to partial restrictions.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%